Unjuk Kerja Evaporator Pada Mesin Pendingin Dengan Siklus Adsorpsi Menggunakan Energi Surya - Amusadar, Amusadar; Hasbi, Muhammad; Samhuddin, Samhuddin (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
Energy needs in Indonesia continue to increase every year. The largest use ofenergy is in the industrial sector, where its needs reach 42.12% of the totalnational energy needs. To save energy, energy saving measures are needed in theindustrial sector so that the increase in energy demand can be restrained. So weconducted research on the performance of the evaporator in a refrigerationmachine with an adsorption cycle using solar energy. The purpose of this studywas to determine the working process of the evaporator with activated carbonrefrigeration and to determine the efficiency of the evaporator in the activatedcarbon pair adsorption refrigeration system. This research was conducted byobserving and recording the evaporator temperature of the refrigeration machineevery hour. The results of the research in three days of testing, namely, on the firstday the highest evaporator temperature increase was at 16.00 o'clock, which was33.2oC and the lowest evaporator temperature was at 07.00 o'clock, which was 25.1 oC. On the second day, the highest increase in evaporator temperature was at 16.00, which was 32.2oC and the lowest evaporator temperature was at 07.00, which was 23.8 oC. On the third day, the highest increase in evaporator temperature was at 36.4 oC and the lowest evaporator temperature was at 06.00,which was 24.5 oC.Kata kunci: Adsorption, evaporator, temperature